Inclusive Distance Antimagic Labeling of Shadow Graph of Complete and Circulant Graph - Siti Hafshah Nurul Arafah; Kiki Ariyanti Sugeng; Debi Oktia Haryeni (Departemen Matematika dan Sains Data FMIPA Universitas Andalas Padang, 2026)
Consider a graph G = (V, E) with order n. Suppose that we have a bijection f: V(G) → {1, 2, ..., n}. A graph G is said to admit an inclusive distance antimagic labeling if every pair of distinct vertices has different weights, with a vertex weight is defined by w(v) = _u N(v) f(u) + f(v). Furthermore, if the vertex weights form an arithmetic progression with the first term a and the common difference d, then G is said to admit an (a,d)-inclusive distance antimagic labeling. This paper investigates the inclusive distance antimagic labeling of the shadow graph of the complete and circulant graph.